(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
Science Communication (SC) is a recent field in the Brazilian context as a field of study. Therefore, SC is defined by researchers through different interpretations. In order to understand such differences for the concept of SC, we carried out exploratory qualitative research, through a narrative review, about the terms used by authors to express the act of communicating Science. We supported our analysis on Linguistics, which made it possible to understand the uses of the term SC and others associated with them, within the Brazilian context. We identified that Science Diffusion is hyperonymous with the expressions Science Dissemination, Communication and Popularization, while the last three establish a synonymous relationship with each other – a result not replicated when observing the definitions in the context of English and French. The results also point divergences regarding meanings depending on the context in which the terms are used. Therefore, we consider that the debate proposed by this research can contribute to the field of Science Communication in Brazil.